Synthesis and Application of Monoazo Acid Dyes Containing Long Chain Perfluoroalkyl Group for Water Repellant Polyamides - Teli, M.D.; Sekar, N.; Prabhu, K.H.; B. Chaudhari, Jitendra (Asian Journal of Chemistry, 2010)
In the present investigation, γ-acid was reacted first with acid chloride namely pentadecafluoro octanoyl chloride, which was synthesized by the reaction with thionyl chloride and pentadecafluoro octaconic acid. The resulting compound was coupled with m-toluidine and thus dye 1F1 of reddish pink hue was synthesized. Similarly in place of m-toluidine, m-trifluromethyl aniline was used with the same intermediate and dye 1F2 with brighter reddish pink was obtained. In case of 2F1 and 2F2 dyes synthesized only the γ-acid in 1F1 and 1F2 was replaced by H-acid. These dyes are brown in shade. The water repellency effect of a long chain derivative containing perfluoro group on the fabric dyed with the synthesized modified monoazo acid dyes was studied.